Temporary Expats for Export: Firm-Level Evidence - Anna Graneli; Magnus Lodefalk (Örebro University School of Business, 2014)
We analyze the relation between temporary expats in firms and exports. Temporary expats are positively associated with exports. The within-firmdestination- country link with export intensity is substantially larger for services than for merchandise and for exports of heterogeneous services and merchandise than for exports of homogeneous products. Additionally, the association with exports is stronger for temporary than for permanent expats. Furthermore, our evidence suggests that temporary expats are positively related to exports by assisting firms in overcoming informal trade barriers. Overall, our findings suggest the importance of the temporary movement of persons for providing firms with up-to-date links to export markets.
Keywords: D80; F10; F20; J60; 330; Expats; temporary movement of persons; migration; networks; firm trade